2022
DOI: 10.1136/jme-2022-108369
|View full text |Cite
|
Sign up to set email alerts
|

Ethical uncertainty and COVID-19: exploring the lived experiences of senior physicians at a major medical centre

Abstract: Given the wide-reaching and detrimental impact of COVID-19, its strain on healthcare resources, and the urgent need for—sometimes forced—public health interventions, thorough examination of the ethical issues brought to light by the pandemic is especially warranted. This paper aims to identify some of the complex moral dilemmas faced by senior physicians at a major medical centre in Saudi Arabia, in an effort to gain a better understanding of how they navigated ethical uncertainty during a time of crisis. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The values, experiences, and desires that exist in each person determine the degree of faith a person has, and faith is the main driver of the manifestation of the sense of obligation and commitment. In line with these results, Muaygil in 2023 reported a sense of obligation and inner commitment existed in the treatment staff for performing care for patients with Covid-19, a commitment that made the treatment staff, in the most difficult and uncertain conditions, recognize their duty and seek to do it [ 20 ]. Although both the present study and Muaygil’s research revealed the existence of an inner requirement and commitment, the strength and distinction of the present study lies in the presence of the divine aspect of this inner commitment, which causes all eyes to turn to the same source, which is God’s satisfaction.…”
Section: Discussionmentioning
confidence: 95%
“…The values, experiences, and desires that exist in each person determine the degree of faith a person has, and faith is the main driver of the manifestation of the sense of obligation and commitment. In line with these results, Muaygil in 2023 reported a sense of obligation and inner commitment existed in the treatment staff for performing care for patients with Covid-19, a commitment that made the treatment staff, in the most difficult and uncertain conditions, recognize their duty and seek to do it [ 20 ]. Although both the present study and Muaygil’s research revealed the existence of an inner requirement and commitment, the strength and distinction of the present study lies in the presence of the divine aspect of this inner commitment, which causes all eyes to turn to the same source, which is God’s satisfaction.…”
Section: Discussionmentioning
confidence: 95%
“…professional commitment to undertake risks for the sake of infected patients can change over time. 15 Empirical studies in recent years have investigated healthcare professionals' attitudes, [16][17][18][19][20][21][22][23] some of which reveal a particular concern about the need for reciprocity, so that the professional's duty to care is matched by societal and institutional duties to protect healthcare professionals (and their families) by providing reasonably safe working conditions. [17][18][19]21,23 Less is known about the beliefs of medical students, [24][25][26][27][28][29] and it is unclear whether and how the emergence of Covid-19 may have affected their attitudes.…”
mentioning
confidence: 99%